7x+9/10=-5x+969/10

Simple and best practice solution for 7x+9/10=-5x+969/10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+9/10=-5x+969/10 equation:


x in (-oo:+oo)

7*x+9/10 = 969/10-5*x // - 969/10-5*x

7*x-(-5*x)+9/10-(969/10) = 0

7*x+5*x+9/10-969/10 = 0

12*x-96 = 0 // + 96

12*x = 96 // : 12

x = 96/12

x = 8

x = 8

See similar equations:

| 5-3x=4x-58 | | -3/5x-3=4x-53/10 | | 1/3+4/7x=-3x+307/21 | | 5/6x+4=4x+245/66 | | 2/3x+2/5=26/15+x | | 2/3x-6=-46/7+5/7x | | -x+1/4=-1/2-3/4x | | 6/7x+4=6x-152/7 | | 3x+5/6=-2x+65/6 | | 1/3x-1/2=-13/6+3x | | x-3/5=-1/2x-3/10 | | 7x+3=43+3x | | 3x+9=-5x+9/5 | | 8+2x=4x+28 | | -7x+2/7=-162/35-6/7x | | -1+6x=x+39/11 | | 1/2x+1/2=-1/2x+7/10 | | 9-2x=1/4x+0 | | -6-4x=x-8 | | 3x+1=19-3x | | x+5/8=27/8+4x | | -6/7x-4/5=141/5-5x | | 1/2x-5=10+2x | | 2/3-x=1/6x+103/60 | | -x-1=-2/3x-3 | | -7+x=1/2x-23/2 | | 6x-2/7=4/5x+172/35 | | 1/4+5x-4x=9/4 | | -8+7x-x=-8 | | 6x+1+4x=-19 | | 2x-2/3-6/7x=-2/3 | | 3/5x+3/10-x=-3/110 |

Equations solver categories